Nanostructured titanium dioxide materials : properties, preparation and applications - Khataee, A. R. (Ali Reza), 1977- (World Scientific Publishing, 2012)
During the past decade, research and development in the area of synthesis and applications of different nanostructured titanium dioxide have become tremendous. This book briefly describes properties, production, modification and applications of nanostructured titanium dioxide focusing in particular on photocatalytic activity. The physicochemical properties of nanostructured titanium dioxide are highlighted and the links between properties and applications are emphasized. The preparation of TiO2 nanomaterials, including nanoparticles, nanorods, nanowires, nanosheets, nanofibers, and nanotubes are primarily categorized by their preparation method (sol-gel and hydrothermal processes). Examples of early applications of nanostructured titanium dioxide in dye-sensitized solar cells, hydrogen production and storage, sensors, rechargeable batteries, electrocatalysis, self-cleaning and antibacterial surfaces and photocatalytic cancer treatment are reviewed. The review of modifications of TiO2 nanomaterials is mainly focused on the research related to the modifications of the optical properties of TiO2 nanomaterials, since many applications of TiO2 nanomaterials are closely related to their optical properties. Photocatalytic removal of various pollutants using pure TiO2 nanomaterials, TiO2-based nanoclays and non-metal doped nanostructured TiO2 are also discussed.